Data Mining Approach: What Determines the Wellbeing of Women in Montenegro, North Macedonia, and Serbia? - Bjegovic-Mikanovic, Vesna; Wenzel, Helmut; Laaser, Ulrich (Frontiers in Public Health, 2022)
Background: Women's happiness and life satisfaction – often summarized as Subjective Well-being - are of great value for most individuals and are associated with various deter-minants. The countries of the Western Balkan are of particular interest after the political changes in the nineties. Are the women satisfied with their lives today? Methods: We use the most recent datasets of the Multiple Indicator Cluster Surveys (MICS) for women 15 to 49 years old and with comparable data coverage for three countries of the Western Balkan belonging to the former Yugoslavia - Montenegro, North Macedonia, and Serbia. After sorting out variables of limited relevance or quality (missing values >50%), the remaining 32 variables – followed a descriptive analysis. Four potential determinants of Subjective Well-being (SWB) - an integration of happiness and satisfaction with life - entered an interactive Classification and Regression Tree (iC&RT) to account for their mostly bivariate format: age, education, region, and wealth. Results: The iC&RT analysis determines the influence of 4 independent variables (age, education, region, and wealth) on overall happiness, satisfaction with life, and Subjective Well-being, resulting in a high overall SWB of 88.9% for Montenegro, 82.1% for North Macedonia, and 83.% for Serbia. The high relevance of younger age, higher education, and wealth as critical determinants of a high SWB and the lesser role of regions except for Ser-bia is confirmed. The spread of SWB in defined population subgroups ranges from 80.5% to 92.6% for Montenegro, 64.2% to 86.8% for North Macedonia, and 75.8% to 87.4% for Serbia. Conclusions: The three selected South-Eastern European countries of the former Yugosla-via (Montenegro, North Macedonia, Serbia) represent high levels of Subjective Well-being of women and a narrow range between the lowest and highest population groups. Females in Montenegro take a top position regarding their Subjective Well-being. Keywords: Subjective Well-being, happiness, satisfaction with life, MICS, Montenegro, North Macedonia, Serbia, women. Conflict of interest: None declared Source of funding: None declared Acknowledgments: We thank Prof. Genc Burazeri, Maastricht University, The Netherlands, for his detailed advice on the analyses in this paper.